PELESTARIAN NILAI-NILAI SPIRITUAL DAN SOSIAL DALAM TRADISI ADAT NGONCANG DI BANJAR ADAT PAKETAN, KELURAHAN PAKET AGUNG, KECAMATAN BULELENG - Wiradnyana I Gd. Arya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Research on conservation in the traditional tradition of ngoncang aims to describe: (1) the history of traditional tradition of ngoncang, (2) spiritual and social values in traditional tradition of ngoncang, (3) strategy in preserving traditional traditions of ngoncang in Banjar Adat Paketan, Kelurahan Paket Agung, Buleleng District. This research is included in qualitative descriptive research. Informants in this research are cultural and community who are involved in traditional ngoncang tradition. Data were collected by interview. Data analysis was conducted by qualitative descriptive method. The results of conservation research in the traditional tradition of ngoncang show that: ngoncang tradition is believed to have existed since the year 1602. For in Banjar Adat Paketan, ngoncang tradition is believed to have emerged since 1876. This is evidenced by the discovery of rice dimple devices in the homes of citizens old enough. Ngoncang habits that have existed since 1876 ago done as an expression of gratitude as well as entertainment after the harvest of rice abundant. The spiritual value embodied in this tradition is that this tradition is a symbol of togetherness and harmony between human and God, man with his fellow human beings and man with his environment, according to which is contained in the teachings of Hinduism namely Tri Hita Karana. The social values contained are togetherness and solidarity. This can be observed in traditional ngoncang processions, which are conducted in groups of five to six people in a group. Everyone is doing the activity of pounding alu into the ketungan. To be able to preserve ngoncang custom it can be done through three ways, namely: (1) performing traditional ngoncang festival, (2) promotion of ngoncang tradition and (3) doing cooperation / partnership with other party Keywords: Traditions,Values, Ngoncang.